Resource geographies 1: Making carbon economies, old and new - Bridge, Gavin (Progress in human geography, 2011)
This progress report is the first in a series of three on resource geographies, and reflects a renewed interest within human geography and cognate disciplines in classic resource questions of scarcity, access and governance. It focuses on carbon, an element which is fast becoming a common denominator for thinking about the organization of social life in relation to the environment. The report examines how researchers are applying one of resource geography’s principle tenets - that so-called ‘natural resources' are an outcome of political, economic and cultural work - to understand the resource-making processes associated with the ‘carbon economy’. Significantly, it expands this term from its limited association with carbon markets and offsetting to encompass the ‘actually existing’ carbon economy associated with the extraction and consumption of fossil fuels. By reading these ‘old’ and ‘new’ carbon economies together, the report considers the making of carbon resources as they extend from the upstream, extractive end of the hydrocarbon commodity chain to the emission, capture and sequestration of carbon downstream. It harnesses the reductionism inherent to ‘carbon’ - its capacity to put apparently different entities on the same page - in order to identify commonalities and connections between the old and new carbon economies that are ordinarily overlooked. The report is organized around three core ‘logics' of resource making that can be identified in recent work: economy, territory and subject formation.